3D Bioprinting of Functional Islets of Langerhans in an Alginate/Methylcellulose Hydrogel Blend. Issue 7 (5th March 2019) - Duin, Sarah; Schütz, Kathleen; Ahlfeld, Tilman; Lehmann, Susann; Lode, Anja; Ludwig, Barbara; Gelinsky, Michael
Abstract: Transplantation of pancreatic islets is a promising strategy to alleviate the unstable blood‐glucose control that some patients with diabetes type 1 exhibit and has seen many advances over the years. Protection of transplanted islets from the immune system can be accomplished by encapsulation within a hydrogel, the most investigated of which is alginate. In this study, islet encapsulation is combined with 3D extrusion bioprinting, an additive manufacturing method which enables the fabrication of 3D structures with a precise geometry to produce macroporous hydrogel constructs with embedded islets. Using a plottable hydrogel blend consisting of clinically approved ultrapure alginate and methylcellulose (Alg/MC) enables encapsulating pancreatic islets in macroporous 3D hydrogel constructs of defined geometry while retaining their viability, morphology, and functionality. Diffusion of glucose and insulin in the Alg/MC hydrogel is comparable to diffusion in plain alginate; the embedded islets continuously produce insulin and glucagon throughout the observation and still react to glucose stimulation albeit to a lesser degree than control islets. Abstract : Primary islets of Langerhans from rat are bioprinted into macroporous 3D structures using an alginate/methylcellulose blend as bioink. The hydrogel blend is comparable to plain alginate in terms of diffusion of glucose and insulin. Plotted islets retain their viability and morphology, continue to produce insulin and glucagon over time in culture, and release insulin in response to glucose stimulation.